Analisis Bibliometrik Perkembangan Penelitian Ulama Ahli Qira’at Al-Qur’an - Dida Maulidah Rukoyah (UIN Sunan Gunung Djati Bandung, 2023)
This study's objective is to learn more about research on bibliometric analysis using dimensions. This study uses bibliometric research to establish a set of quantitative methods for analyzing scientific publications about Islamic scholars of qira'at. carried out in this study. Namely determination of keywords, data search, article selection, data validation, data analysis with Visualization. This study uses data from international publications about Islamic scholars of qira at al-Qur'an which are sourced from data dimensions. In the data dimensions there are four categories, namely in the research category Qira'at Expert Scholars are dominantly researched in the fields of Philosophy and Religious Studies and in the fields of History and Archeology. The research development trend of Qira'at Expert Ulama tends to increase every year with the highest number of studies occurring in 2019. There are no dominant researchers and even tend to be evenly distributed regarding the number of publications, namely at most 2 publications, namely Cut Fauziah, Ibnu Rawandhy N. Hula, Thoriq Aziz Jayanya and the most numerous is Suarni Suarni with a total of 4 publications. Places of publication for Islamic Theology research are dominated by the Scientific journal Al-Muashirah, Journal of Al-Qur'an Sciences and Tafsir and Al-Bayan Journal of Study of Al-Qur'an Sciences and Tafsir.